Alur Ceria Pembelajaran Bahasa Inggris Kelas X SMA dalam Konteks Implementasi Kurikulum Merdeka - Mulyani, Mulyani (Universitas Muhammadiyah Ponorogo, 2023)
In the practice of learning English, based on the author’s observations, it was found that there are still most high school English teachers who have difficulty understand and implementing independent curriculum designs. The results of the discussion at the district level high school English MGMP (Subject Teacher Consultation) level can be concluded that the change in the independent curriculum has caused difficulties for high school English teachers in understanding the differences with the 2013 curriculum. One of them is the difficulty in understanding learning achievement document and the flow in teach material. To practice or try out the application of an independent curriculum for high school English subjects in classroom learning, it is necessary to do a creativity or innovation from the teacher do that the pattern and flow of learning can be understood correctly. One thing that can be considered in implementing high school English learning based on learning achievement elements is through the CERIA (Choose, Explore, Resume, Inform, and Apply) flow. This flow makes it easier for teachers and students to develop language elements in an integrated manner.